Marketing plans profitable strategies in the digital age - McDonald, Malcolm; Chaffey, Dave 1963-; Wilson, Hugh 1962- (Wiley, 2024)
This book is in its 8th edition and has sold thousands of copies over many years The topic of marketing planning is on every curriculum in the world and this is the accepted, standard text on the topic. New world leading material on customer experience management drawing on several years research with experience leading blue-chips in Cranfield and Warwick. The authors are publishing on that in the world's top marketing journals, so aiding adoption"--